Economy, Business and Uncertainty: New Ideas for a Euro-Mediterranean Industrial Policy - Gil-Lafuente, Jaime; Marino, Domenico; Morabito, Francesco Carlo (Studies in Systems, Decision and Control, 2019)
This book presents original research articles addressing various aspects of economics, management and optimization. The topics discussed include economics, finance, marketing, resource allocation strategies, fuzzy logic, and network-based techniques for the analysis of economics, management and mathematical optimization. Combining the input of contributing professors and researchers from various Spanish, Italian and Latin American universities, the book will be of interest to students, researchers and practitioners, as well as members of the general public interested in the world of Economics and Management.